2003
DOI: 10.1046/j.1365-313x.2003.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional response of Arabidopsis to genotoxic stress – a high‐density colony array study (HDCA)

Abstract: SummaryA genome-wide transcription pro®ling of Arabidopsis upon genotoxic stress has been performed using a high-density colony array (HDCA). The array was based on a library of 27 000 cDNA clones derived from Arabidopsis cells challenged with bleomycin plus mitomycin C. The array covers more than 10 000 individual genes (corresponding to at least 40% of Arabidopsis genes). After hybridisation of the HDCA with labelled cDNA probes obtained from genotoxin-treated (bleomycin plus mitomycin C, 6 h) and untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 55 publications
(46 reference statements)
3
113
0
1
Order By: Relevance
“…It is worth noting that CYCB1;1, but not other mitotic cyclins, are up-regulated after DNA-damaging treatment (Chen et al, 2003). A similar response is observed after aphidicolin-induced replication stress, which is not displayed in the atr mutants, defective in the G2 checkpoint (Culligan et al, 2004).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It is worth noting that CYCB1;1, but not other mitotic cyclins, are up-regulated after DNA-damaging treatment (Chen et al, 2003). A similar response is observed after aphidicolin-induced replication stress, which is not displayed in the atr mutants, defective in the G2 checkpoint (Culligan et al, 2004).…”
Section: Discussionmentioning
confidence: 68%
“…Both pathways are largely conserved in Arabidopsis and rely on a transduction cascade dependent on ATM and ATR gene products (Garcia et al, 2003;Culligan et al, 2004). Transcriptional up-regulation of certain genes in these pathways is a hallmark of plant DNA damage checkpoint response (Chen et al, 2003;Lafarge and Montane, 2003;DeBlock et al, 2005). We found that the mRNA levels of Ku70, which participates in the G1 checkpoint and NHEJ, did not change.…”
Section: Cdka Activity Is Reduced In Caf-1-deficient Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works have been reported on gene regulation of DNA repair genes in response to DNA damage (Chen et al 2003;Molinier et al 2005). However, the promoter functions of DNA repair genes that direct tissue specific and DNA damage-responsive gene expression are not necessarily clear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works of DNA repair-related plant genes involved in response to treatment with DNA damaging agents revealed that the induction level of AtRAD51 gene is one of the best among the up-regulated genes that respond to DNA damage (Chen et al 2003;Molinier et al 2005). In order to investigate the DNA damage response of AtRAD51 promoter, a radiomimetic bleomycin, which is known to induce mostly DSBs (Menke et al 2001), and the UV-B radiation, which is reported to result in increased frequencies of homologous recombination in plant (Ries et al 2000), were employed as DNA damaging agents.…”
mentioning
confidence: 99%